2022
DOI: 10.1001/jamanetworkopen.2022.21509
|View full text |Cite
|
Sign up to set email alerts
|

Association Between State Supplemental Nutrition Assistance Program Policies, Child Protective Services Involvement, and Foster Care in the US, 2004-2016

Abstract: Key Points Question Are state Supplemental Nutrition Assistance Program (SNAP) policy options associated with rates of Child Protective Services involvement and use of foster care services in the US? Findings This cohort study including all 50 states and the District of Columbia noted that adoption of SNAP policies increased from 2004 to 2016 and, accompanying the increases, substantiated reports of childhood neglect decreased. In instrumental variables mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
(80 reference statements)
1
14
0
Order By: Relevance
“…Under BBCE, states have the option to eliminate the asset test used to determine SNAP eligibility and/or to increase the income limit for SNAP eligibility from 130% to up to 200% of the federal poverty level . A recent study examined state adoption of 4 SNAP eligibility and enrollment policies, including a single indicator for whether states increased the income limit or eliminated the asset test under BBCE. This study found that the BBCE indicator was associated with reductions in rates of CPS-investigated reports .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under BBCE, states have the option to eliminate the asset test used to determine SNAP eligibility and/or to increase the income limit for SNAP eligibility from 130% to up to 200% of the federal poverty level . A recent study examined state adoption of 4 SNAP eligibility and enrollment policies, including a single indicator for whether states increased the income limit or eliminated the asset test under BBCE. This study found that the BBCE indicator was associated with reductions in rates of CPS-investigated reports .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study examined state adoption of 4 SNAP eligibility and enrollment policies, including a single indicator for whether states increased the income limit or eliminated the asset test under BBCE. This study found that the BBCE indicator was associated with reductions in rates of CPS-investigated reports . However, because states can adopt 1 or both BBCE policies, understanding their association—individually and combined—with CPS involvement is important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a quantitative policy analysis, Johnson-Motoyama and colleagues examine the association of state policies governing the Supplemental Nutrition Assistance Program (SNAP) with CPS involvement and foster care placement in the US. Their econometric analysis shows that states with more income generosity policies related to SNAP observed decreases in reported child maltreatment and neglect, substantiated cases, and intake into foster care.…”
mentioning
confidence: 99%
“…However related they may be, food insecurity and child maltreatment are both cause and consequence of distal social-ecological dynamics that affect the health and well-being of children, families, and communities, as Belsky argued so convincingly in his classical 1980 article on the ecology of child maltreatment. Expanding Bronfenbrenner’s ecological systems theory, Belsky reported that child maltreatment is “multiply determined by forces at work in the individual (ontogenic development) and the family (the microsystem), as well as the community (the exosystem), and the culture (the macrosystem) in which both the individual and family are embedded.” Johnson-Motoyama et al add empirical evidence that macrosystem policies such as SNAP prevent child maltreatment and the need for foster care, especially the more generous these policies are. This evidence must be contextualized within the larger contemporary body of research on associations between child maltreatment and individual, family, and neighborhood poverty; housing instability; food insecurity; structural racism and injustice; and socioeconomic inequities and inequalities …”
mentioning
confidence: 99%